Legal Analysis of Cash Waqf-Based Real Estate Development in Indonesia: Integrating Sharia Principles with Contemporary Business Law - Yuherman; Yuhelson; Radif Khotamir Rusli (JURNAL ILMIAH LIVING LAW, 2025)
This study provides a comprehensive legal analysis of the regulatory framework governing cash waqf-based real estate development projects in Indonesia. It critically examines the integration of Sharia principles with contemporary Indonesian business law, focusing on the legal challenges and opportunities that arise from this intersection. The research employs a normative legal approach, analyzing statutory provisions, recent jurisprudence from 2022-2024, and relevant fatwas from the National Sharia Council (DSN-MUI). Key findings reveal significant regulatory gaps, including overlapping institutional authorities, weak enforcement mechanisms, and a lack of harmonization between Law No. 4 of 2004 on Waqf and Law No. 2 of 2008 on Islamic Banking. The study further explores the role of innovative financial instruments, such as Cash Waqf-Linked Sukuk (CWLS), and the impact of recent OJK regulations on the participation of Islamic banks in waqf-based projects. By offering a detailed analysis of these legal dynamics, the research proposes a multi-faceted strategy to enhance legal certainty, strengthen governance, and unlock the full potential of cash waqf for sustainable and inclusive real estate development in Indonesia. The paper concludes with actionable recommendations for policymakers, regulators, and practitioners to foster a more robust and Sharia-compliant ecosystem for waqf financing.